2011
DOI: 10.1891/0889-7182.25.1.55
|View full text |Cite
|
Sign up to set email alerts
|

A Process of Decision Making by Caregivers of Family Members With Heart Failure

Abstract: Heart failure (HF) is a major cardiovascular problem and the number of people living with HF continues to climb. Throughout the illness continuum, patients and their family caregivers are involved in decision making. As the illness worsens and patients can no longer make decisions, decision making becomes the responsibility of their caregivers who may have little preparation for the role. The purpose of this grounded theory study was to examine how caregivers of family members with HF make decisions. A nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Though caregivers provided substantial support, as noted above, for medication adherence and sodium avoidance, very few studies cited caregiver assistance with other aspects of self-care as recommended by clinical guidelines, such as daily weighing,44 fluid restriction,44 physical activity42 or timely help-seeking 19 63. These facets of self-care were also not commonly cited by patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though caregivers provided substantial support, as noted above, for medication adherence and sodium avoidance, very few studies cited caregiver assistance with other aspects of self-care as recommended by clinical guidelines, such as daily weighing,44 fluid restriction,44 physical activity42 or timely help-seeking 19 63. These facets of self-care were also not commonly cited by patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although caregivers saw their role as indisputable and rewarding,61 64 they could also feel socially isolated, distressed,61 64 fatigued51 and ill-prepared64 for the demands of caregiving. Indeed, patients and caregivers cited a need for greater informational support for caregivers 51 63 64 75. For example, although caregivers in one study reported monitoring patients for peripheral oedema, the same caregivers did not report monitoring fluids or sodium intake or indicate knowledge of the links among these 19.…”
Section: Resultsmentioning
confidence: 99%
“…Although the literature suggests significant influence derived from culture, family and friends on healthcare decisions [23][24][25], focus group participants did not perceive the social network domain to have a large influence on their decisions at the point of care. Friends and family were more likely to influence pre-and postencounter decisions.…”
Section: Discussionmentioning
confidence: 77%
“…The progression of the disease heightens the burden of responsibility on the family caregiver, regarding the decisions that must be taken and in many cases initiates a progressive sequence of impaired ability to cope with the situation, ultimately having a negative impact on the patient (Sanford et al 2011). The study follow up will continue for 18 months, which is considered sufficient time to detect such changes in the patient-caregiver dyad.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the disease progresses, decisions must increasingly be taken by the family caregivers and they are sometimes overwhelmed by this situation (Sanford et al 2011). However, some interesting studies have also shown there is a positive effect in exercising the caregiver role (O'Reilly et al 2008, Brown et al 2009).…”
Section: Introductionmentioning
confidence: 99%